Bio-inspired polymer envelopes around adenoviral vectors to reduce immunogenicity and improve in vivo kinetics. (15th January 2016) - Fan, Gerui; Fan, Minmin; Wang, Qin; Jiang, Jiayu; Wan, Yu; Gong, Tao; Zhang, Zhirong; Sun, Xun
Graphical abstract: Abstract: Adenoviral vectors have attracted substantial interest for systemic tumor gene therapy, but further work is needed to reduce their immunogenicity and alter their biodistribution before they can be used in the clinic. Here we describe a bio-inspired, cleavable PEGylated β-cyclodextrin-polyethyleneimine conjugate (CDPCP) that spontaneously coats adenovirus in solution. This cleavable PEG coating reduces the innate and adaptive immunogenicity of adenovirus particles, as well as improves their biodistribution away from the liver and into the tumor. Insertion of a matrix metalloproteinase substrate sequence into the conjugate allows PEG cleavage at the tumor site, simultaneously reducing liver biodistribution and increasing transgene expression in tumors, thereby avoiding the "PEG dilemma". Cationic β-cyclodextrin–PEI not only provides electrostatic attraction to promote envelope attachment to the viral capsid, but it also improves vector internalization and transduction after PEG cleavage. These results suggest that CDPCP may help expand the use of adenoviral vectors in cancer gene therapy. Statement of significance: The synthesized β-cyclodextrin–PEI-MMP-cleavable-PEG polymer (CDPCP), held great potential for gene therapy when applied for adenovirus coating. The β-cyclodextrin–PEI provided a powerful electrostatic attraction to attach the whole polymer onto the viral capsid, while the MMPs-cleavable PEG reduced innate and adaptive immunogenicity and improved the biodistribution of adenovirus vectors due to the tumor-specific enzyme triggered PEG cleavage. More importantly, an ingenious cooperation between the two components could solve the PEG dilemma. The CDPCP/Ad complexes exhibited a comprehensive and valued profile to be a candidate vector for future tumor gene therapy, we believe the current investigation on this kind of biomaterial may be of particular interest to the readership of Acta biomaterialia.